Natural history of brucellosis in an endemic region in different time periods - Bosilkovski, Mile; Dimzova, Marija; Grozdanovski, Krsto (My University, 2009)
The aim of the study was to determine the evolution and outcome of human brucellosis in an endemic region in relation to time interval. Retrospective analysis was employed to compare demographic, epidemiological, clinical, laboratory features and the outcome of patients with brucellosis, treated at University Department of Infectious Diseases in Skopje during two different periods of time. A series of 159 patients were studied in the first (1990-1991) and 138 in the second (2003-2005) study period. Patients treated in the second period were older (34.6+/-20.9 vs. 30.0+/-17.7 years; P=0.041) and acquired brucellosis less frequently on ingestion of incriminated food (34.8% vs. 47.2%; P=0.031). Focal forms were more evident in the second period (66.7% vs. 50.3%; P=0.004), mainly due to osteoarticular localization. Post-treatment follow up was more efficient in the second group (76.1% vs. 61%; P=0.005). There was no difference according to disease outcome in spite of different therapeutic trials during the two study periods. In conclusion, the established differences showed an improvement in the understanding of the disease by the general population as well as upgrading of some aspects considering medical activities. Nevertheless, this endemic region still lacks the most important measure, i.e. development and implementation of an appropriate national program for efficient control of the disease.